Experimental context classification: incentives and experience of subjects - Höst, Martin; Wohlin, Claes; Thelin, Thomas (Proceedings of the 27th international conference on Software engineering, 2005)
There is a need to identify factors that affect the result of empirical studies in software engineering research. It is still the case that seemingly identical replications of controlled experiments result in different conclusions due to the fact that all factors describing the experiment context are not clearly defined and hence controlled. In this article, a scheme for describing the participants of controlled experiments is proposed and evaluated. It consists of two main factors, the incentives for participants in the experiment and the experience of the participants. The scheme has been evaluated by classifying a set of previously conducted experiments from literature. It can be concluded that the scheme was easy to use and understand. It is also found that experiments that are classified in the same way to a large extent point at the same results, which indicates that the scheme addresses relevant factors.